Effect of Sowing Dates, Intra-Row Spacings and Nitrogen Fertilizers of the Productivity of Red Variant Roselle (Hibiscus sabdarifa L) - F. E., Babatunde; T. O., Oseni; B. M., Auwalu; G. N., Udom (Universiti Putra Malaysia Press, 2002)
Field experiments were conducted during the rainy seasons (June - Odober) of 1999 and 2000, at the research farm of Abubakar Tafawa Balewa University, Bauchi, Nigeria to study the effects of some agronomic practices on the growth and yield of roselle. Three agronomic practices (sowing dates, intra-row spacing and nitrogenous fertilizer levels) at three levels each, were factorially combined to give a total of 27 treatment combinations. These were laid out in a randomized complete block design with three replications. Most of the results obtained were highly significant (P50.01). Sowing dates (June) gave the highest mean calyx (2035.15 kg/ha) and seed (2391.19 kg/ha) yields in both years. Intra-row spacing (80 em) gave the highest mean calyx (1651.11 kg/ha) and seed (2024.40 kg/ha) yields. Also, application of 60 kg N/ha gave the highest mean calyx (1671.99 kg/ha) and seed (2067.36 kg/ha) yields. It is evident from the results of this experiment that, the earlier the sowing of dates, the wider the intra-row spacing and the higher the nitrogenous fertilizer level, the higher the productivity of red variant roselle. Sequel to these facts, roselle sown in June at intra-row spacing of 80 em should be applied with 60 kg N / ha for optimum productivity in the study area.